Relationship between internet addiction and sleep quality in the students of Ilam University of Medical Sciences in 2023. - Jalilian, Mohsen; Pakzad, Reza; Mirzaei, Amin; Saeedfiroozabadi, Malihe; Maleki, Hadis; Shahbazi, Parisa; Khorshidi, Ali; Chenary, Roghayeh (Journal of Basic Research in Medical Sciences, 2024)
Introduction: Today, internet usage has become an integral part of daily life, but excessive use can harm sleep quality. This study aims to explore the relationship between internet addiction and sleep quality among students at Ilam University of Medical Sciences in 2023. Material & Methods: In 2023,400 students from Ilam University of Medical Sciences participated in this study. They were selected using simple random sampling and met the study criteria. Data were collected through Young's Internet Addiction Test (IAT) and the Pittsburgh Sleep Quality Index (PSQ1). Simple and multiple regression analyses were conducted with a significance level of a ≤ 0.05. Results: The findings showed that 320 (80%) of students exhibited mild to severe internet addiction, with an average total sleep quality falling within the poor range (6.30 ± 2.51). Subjective sleep quality was particularly poor (2.03 ± 0.662) compared to other dimensions (p > 0.05). Simple linear regression revealed significant associations between mild (coefficient = 1.03; p = 0.002) and moderate (coefficient = 2.05; p < 0.001) internet addiction and poor total sleep quality, compared to normal individuals. Additionally, graduate students had better sleep quality than undergraduates (coefficient = -1.03; p = 0.016). Multiple regression analysis, adjusted for educational level, confirmed the association between mild (coefficient = 0.98; p = 0.003) and moderate (coefficient = 1.97; p < 0.001) internet addiction and poor total sleep quality. Conclusion: Internet addiction is linked to poor sleep quality among Ilam University of Medical Sciences students, especially undergraduates. It underscores the need for interventions to raise awareness about internet addiction and its detrimental effects on sleep quality.